Penggunaan Aplikasi Canva dalam Media Pembelajaran Matematika di Sekolah Dasar - Miftahul Jannah, Feryana N; Nuroso, H; Mudzanatun, Mudzanatun; Isnuryantono, E (Jurnal Pendidikan Dasar, 2023)
This literature review is to analyze scientific articles related to the effectiveness of using Canva as a learning medium for students, especially in mathematics. Canva is a free platform that provides graphic design. The method used is the literature review method which is sourced from articles in Google Scholar. The scientific articles used in this literature review are within the last 5 years (2018-2022). Today's learning does not only utilize objects that can be found in the environment around us but can take advantage of the digital world. Canva is an application that can be used in the process of making mathematics learning media that really needs media to convey messages from abstract learning material content. The Canva application provides a variety of interesting features that can make it easier for teachers to create learning media, one of which is the availability of various templates that can be used in the process of designing learning media, one of which is elementary mathematics. The research implementation uses the literature review method through the process of placing, obtaining, reading, and evaluating various research literature related to or related to the problem to be studied. The data described are the results of research regarding the effectiveness of using the Canva application that has been carried out by previous researchers.